2012
DOI: 10.1136/heartjnl-2012-302843
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis of elderly patients with AF in the UK: an analysis using the General Practice Research Database (GPRD) 2000-2009

Abstract: ObjectiveTo assess use of thromboprophylaxis in UK general practise among patients with atrial fibrillation (AF); to investigate whether elderly patients are less likely to receive anticoagulation therapy than younger patients.DesignRetrospective cohort studySettingUK General Practice Research Database (GPRD)PatientsAged ≥60 years with a new diagnosis of AF (2000–2009).InterventionsNone.Main outcome measuresThe main outcome measure was initiation of warfarin in the first year following diagnosis. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 33 publications
7
74
0
3
Order By: Relevance
“…More interesting, the distribution of the percentages of patients treated with VKAs across the cells defined by the scores (Table 3) and the results of the logistic analyses showed that the patient's bleeding risk, but not the cardio-embolic risk alone, predicted the therapeutic choice. These findings on the relationship between the bleeding score and VKA prescription are consistent with those of the UK cohort [5]. In the literature, evidence on the relationship between cardio-embolic scores and VKA prescription in real settings is not uniform [5,23,24].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…More interesting, the distribution of the percentages of patients treated with VKAs across the cells defined by the scores (Table 3) and the results of the logistic analyses showed that the patient's bleeding risk, but not the cardio-embolic risk alone, predicted the therapeutic choice. These findings on the relationship between the bleeding score and VKA prescription are consistent with those of the UK cohort [5]. In the literature, evidence on the relationship between cardio-embolic scores and VKA prescription in real settings is not uniform [5,23,24].…”
Section: Discussionsupporting
confidence: 78%
“…There was also a high representation of the high risk category for bleeding among REPOSI patients, higher than in the UK cohort [5]. As for the cardio-embolic scores, a reclassification effect with HAS-BLED was observed compared to HEMORR 2 HAGES.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations